Occupational Therapy Drawing Activities and TAK Perceptual Stimulation on Hearing Hallucination Changes in Schizophrenia Patients - Zakia, M Ghaulan; Warni, Hernida; Deadora, Miranti (Sarana Ilmu Indonesia (salnesia), 2025)
Hallucinations are one type of mental disorder in which the patient experiences changes in sensory perception, feeling false sensations in the form of sound, sight, taste, touch or smell. The most common hallucination is auditory hallucination, reachingapproximately 70%. The study aimed to determine the effectiveness of drawing activity occupational therapy as the intervention group and perceptual stimulation group activity therapy as the control group on changes in auditory hallucinations in schizophrenia patients at Aulia Rahma Clinic in 2024. This study design used a quantitative study with a Quasi-Experimental design, Two Group Pretest-Posttest approach. The number of samples was 38 (19 intervention groups and 19 control groups) with purposive sampling technique. This study was conducted by conducting pretest and posttest (Drawing Activity Occupational Therapy and Group Activity Therapy Session I-V). The data were analyzed using paired t-test and independent t-test with a significance level of 95% (p-value < 0,05). The result indicated that the significant effectiveness of both therapies in reducing symptoms of auditory hallucinations with p-value <0,001. Drawing activity occupational therapy showed significantly greater symptom reduction compared to group activity therapy. Both therapies are recommended to overcome auditory hallucinations in schizophrenia patients, with special consideration on the effectiveness of group activity therapy. It is suggested that Aulia Rahma Clinic develop a comprehensive occupational therapy program, with a focus on drawing activities.